FLUID BALANCE AND ITS IMPACT ON NERVOUS SYSTEM FUNCTION: NEUROENDOCRINE AND MORPHOLOGICAL ASPECTS - Hazratov E’zoz Erkin ugli (Web of Journals Publishing, 2025)
Fluid balance plays a crucial role in maintaining the proper functioning of the nervous system. Disruptions in fluid homeostasis can lead to significant neurological consequences, affecting both the central and peripheral nervous systems. This article explores the neuroendocrine regulation of fluid balance and its impact on neuronal morphology and function. Additionally, we discuss the pathological implications of fluid imbalance, including dehydration, cerebral edema, and electrolyte disturbances, which can contribute to various neurological disorders such as migraines, seizures, and neurodegenerative diseases. Understanding the interplay between fluid homeostasis and nervous system function provides valuable insights for the diagnosis, prevention, and treatment of neurologically related fluid disorders.
Keywords: Fluid balance, nervous system, neuroendocrine regulation, neuronal morphology, electrolyte imbalance, cerebral edema, dehydration, neurological disorders, neurophysiology.